Re-Viewing, Re-Imaging, and Re-Invigorating Middle School Teacher Education - Edward Podsiadlik III (Middle Grades Review, 2016)
How do we best prepare educators for teaching in the middle grades? This essay reviews authentic middle student feedback and two comprehensive units of instruction in order to re-view and re-imagine the potential of middle school teacher education to become re-invigorated in its capacity to offer relevant and critical instructional experiences. Essential questions explored are: 1) what do effective middle school teaching and learning uniquely look and sound like?; and 2) what singular components, considerations, and challenges does middle school teacher education need to specifically address? Evidence is examined that demonstrates pedagogical components, strategies, and a wide-range of resources which exemplify instructional planning and decision-making specific to meaningful middle school instruction. Specific implications and recommendations for teacher education are offered that address considerations specific to providing middle school instruction relevant to contemporary student lives and pertinent to their (individual and collective) emerging and evolving identities and values.
Keywords: middle school; teacher education; pedagogy; instructional practices; strategies; resources